Health behaviour of adolescents in Slovenia - Zorko, Maja (Obzornik zdravstvene nege, 2014)
Introduction: Monitoring of health behaviours, especially of adolescents, is essential for the future of each nation. Over the last decades, many changes have occurred in all aspects of our lives, affecting the health and quality of life of all people, including children and adolescents. Methods: The study is based on a quantitative research method. The survey was conducted on a representative sample of Slovenian 11-, 13- and 15-year-old adolescents, using a standardised international questionnaire (HBSC study - Health Behaviour in School-Aged Children). The survey was carried out with the assistance of school counsellors in the spring of 2002, 2006 and 2010 (n = 15.080). For determining the correlation between two individual years, the chi-square test was used. The significance level was calculated using the statistical significance value of p < 0.05. Through the Cochran-Armitage trend test, it was established whether a trend existed for the selected indicators in the period between 2002 and 2010. Results: There are some favourable trends, e.g. eating breakfast (p = 0.000), tooth brushing (p = 0.000), lower proportion of individuals who rate their health as poor (p = 0.002) and experience several psychosomatic symptoms (p = 0.000), but also unfavourable trends, e.g. decrease in physical activity (p = 0.023), increase in early alcohol consumption (p = 0.000), dissatisfaction with school (p = 0.000) and bullying others (p = 0.000). Discussion and conclusion: The conclusions of the analyses can serve as a useful basis for further work and development of systemic measures to promote healthy behaviours and prevent risky and unhealthy behaviours among children and adolescents.
Keywords: adolescents; behaviour; mladostniki; samoocena zdravja; self-rated health; trendi; trends; vedenje